MENELISIK PERKAWINAN TIDAK TERCATAT DAN DI BAWAH UMUR DI KOTA YOGYAKARTA - Fakhruddin Fakhruddin (Harmoni, 2015)
This study uses qualitative approach with observation and in-depth interview as data collection. Unrecorded and earlier or child marriage occur because of sexuality and economic factors. Sexuality factor is the important variable because it causes some problems such as marriage, divorce, and family conflicts. Moreover, consumptive life style and pragmatic life that are influenced by media and information change society toward marriage. It can be concluded that economic condition, life styles, and pragmatic life can cause sexuality, therefore the unrecorded and child marriage increase in Yogyakarta. Those phenomenon and cultures show that society tends to be pessimistic in their social environment.